Effect of the Duration of NSAID Use on COVID-19 - Kim, Kyeongmi; Yoon, Siyeoung; Choi, Junwon; Lee, Soonchul (Medicina (Lithuania), 2022)
Background and Objectives: Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to control pain and fever. However, their effect on COVID-19 infected patients has not been fully studied. In this study, we investigated the effect of the duration of NSAIDs use on COVID-19 infection and clinical outcomes. Materials and Methods: In South Korea, 25,739 eligible patients who received COVID-19 testing between 1 January and 31 July 2020, were included in this retrospective observational cohort analysis. Based on the date of the first COVID-19 test for each patient, NSAID prescription dates were used to separate patients into two groups (short-term group: <2 weeks; long-term group: 8–12 weeks). COVID-19 infectivity and clinical outcomes were analyzed. We used the propensity score-matching (PSM) method. Results: Of the 580 patients who had taken NSAIDs before the date of COVID-19 test, 534 and 46 patients were grouped in the short- and long-term NSAID-use groups, respectively. We did not find a statistically significant increased risk of COVID-19 infection (adjustment for age and sex, p = 0.413; adjustment for age, sex, region of residence, comorbidity, Charlson Comorbidity Index, and current use of medication, p = 0.259) or change in clinical outcomes, including conventional oxygen therapy, admission of intensive care unit, artificial ventilation, or death, between the two groups in which the PSM method was applied. Conclusions: The duration of NSAIDs use did not have a statistically significant effect on COVID-19 infectivity or clinical outcomes. However, further studies looking at clinical presentation and laboratory test results in a large number of people should be performed.
Keywords: Anti-Inflammatory Agents, Non-Steroidal; Cohort Studies; COVID-19; COVID-19 Testing; Humans; Retrospective Studies; COVID-19; duration; NSAID